Study of stress and anxiety on quality of life - Rai, Prithi Bahadur; Chaudhary, Birenda Kumar; Bhatta, Binash (Journal of Karnali Academy of Health Sciences, 2026)
Introduction: Stress and anxiety are among the most prevalent psychological conditions globally and are known to adversely affect quality of life (QoL). Despite the high burden of mental illness in Nepal, localized evidence on the relationship between perceived stress, anxiety severity, and multidimensional QoL in tertiary psychiatric settings remains scarce. Methods: This cross-sectional analytical study was conducted at Biratnagar, Nepal, among 262 consecutive patients attending the Psychiatry OPD and ward. Perceived stress, anxiety, and QoL were measured using the Perceived Stress Scale-10 (PSS-10), Hamilton Anxiety Rating Scale (HAM-A), and WHOQOL-BREF, respectively. Pearson correlation, one-way ANOVA, and multiple linear regression were used for analysis. Results: The mean PSS-10 score was 24.22 ± 7.20, with 139 (53.1%) having moderate and 104 (39.7%) high perceived stress. The mean HAM-A score was 24.48 ± 9.17, with 136 (51.9%) classified as having severe anxiety. The psychological domain recorded the lowest mean QoL score (41.16 ± 18.23) and the environmental domain the highest (51.95 ± 15.30). PSS-10 showed statistically significant negative correlations with the psychological (r = -0.124, p = 0.044) and social relationships (r = -0.152, p = 0.013) domains. HAM-A did not significantly correlate with any QoL domain. The regression model was non-significant (R² = 0.021, p = 0.357). Conclusion: Psychiatric patients in this tertiary setting carry a high burden of stress and anxiety, with perceived stress selectively impairing psychological and social QoL. Future studies should incorporate social support, diagnosis type, and treatment variables to better predict QoL in this population.